2013
DOI: 10.1093/occmed/kqt019
|View full text |Cite
|
Sign up to set email alerts
|

Predicting return to work following treatment of chronic pain disorder

Abstract: Workers compensation boards should refer injured workers with CPD to treatment programmes as early as possible to achieve a successful RTW. Additionally, RTWCs play an important role in improving work outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 23 publications
2
12
0
2
Order By: Relevance
“…5 The RTW approach uses comprehensive onsite programs involving work accommodation, which has proven to reduce the duration of work-related disability in comparison to earlier approaches of vocational rehabilitation. 6 Work accommodation can include lighter duties, shorter work hours, changed workstation, or a different job with the same employer, and aims to temporarily meet the workers' needs while recovering. 7 The literature on RTW outcomes and factors involved in the course of disabled workers through the disability management process is extensive.…”
Section: Introductionmentioning
confidence: 99%
“…5 The RTW approach uses comprehensive onsite programs involving work accommodation, which has proven to reduce the duration of work-related disability in comparison to earlier approaches of vocational rehabilitation. 6 Work accommodation can include lighter duties, shorter work hours, changed workstation, or a different job with the same employer, and aims to temporarily meet the workers' needs while recovering. 7 The literature on RTW outcomes and factors involved in the course of disabled workers through the disability management process is extensive.…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as age [25], sex (female) [3, 4, 6], level of education [4], economic status [6], severity of disease [2, 4], starting point of treatment [2], duration of convalescence [4, 5, 7], handicap level [5–7], working duration [2, 3, 5, 7], size of workplace [3, 5], occupational category [3, 5, 7], average wages [5], type of employment [7], and intervention for returning [8] have been described as important elements. Recent studies have shown that psychological elements—including self-efficacy, coping skill, disability acceptance, and depression—have a relationship with returning to work.…”
Section: Introductionmentioning
confidence: 99%
“…Vocational professionals have an important and sometimes critical role to play in the RTW process. These professionals go under a variety of names, e.g., vocational therapists/consultants/case coordinators/counsellors (VTs) [ 11 , 56 , 93 , 98 , 121 ], or sometimes return to work coordinators [ 89 , 122 ]. Their prime functions include matching the abilities and aspiration of the client with the demands of employment [ 36 , 60 , 93 , 98 ].…”
Section: Some Key Ingredients To Successful Vrmentioning
confidence: 99%
“…Firstly, the appropriate timing of the health intervention [ 1 , 124 ] and secondly, the early focus in RTW planning [ 1 , 66 ]. Often both factors apply [ 122 ]. This is clearly seen in management of musculoskeletal disorders, where they remain common [ 1 , 66 ], but also in the management of TBI [ 60 ], multiple sclerosis [ 99 ], mental health [ 100 ] and chronic pain [ 122 ], etc.…”
Section: Some Key Ingredients To Successful Vrmentioning
confidence: 99%